2013
DOI: 10.1109/tste.2012.2202929
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Model Predictive Control of a Point Absorber Wave Energy Converter

Abstract: This paper presents the application of nonlinear model predictive control (NMPC) to a point absorber wave energy converter (WEC). Model predictive control (MPC) is generally a promising approach for WECs, since system constraints and actuator limits can be taken into account. Moreover, it provides a framework for defining optimal energy capture and it can benefit from predictions. Due to possible nonlinear effects, such as the mooring forces, an NMPC is proposed in this paper, whose performance is compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
130
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(135 citation statements)
references
References 19 publications
1
130
0
Order By: Relevance
“…In Fusco and Ringwood (2012) and Fusco and Ringwood (2010), different prediction algorithms for short term wave forecasting are presented. Linear and non-linear MPC for different types of wave energy absorbers are introduced in Cretel et al (2011);Brekken (2011);Hals et al (2010); Richter et al (2013), where it is indicated that the MPC is a promising controller for increasing the power outtake of WECs.…”
Section: Introductionmentioning
confidence: 99%
“…In Fusco and Ringwood (2012) and Fusco and Ringwood (2010), different prediction algorithms for short term wave forecasting are presented. Linear and non-linear MPC for different types of wave energy absorbers are introduced in Cretel et al (2011);Brekken (2011);Hals et al (2010); Richter et al (2013), where it is indicated that the MPC is a promising controller for increasing the power outtake of WECs.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, WPEA's based on the idea of Model Predictive Control (MPC) have attained increasing focus from the wave energy research community, see e.g., [4][5][6][7][8][9][10][11], and initial results are encouraging: MPC may lead to increased energy output of a WEC compared to e.g., reactive control WPEA. In the early work of [4,6,8], a linear MPC has been developed and simulated on ideal PTO systems harvesting energy of point absorber WEC's.…”
Section: Introductionmentioning
confidence: 99%
“…This is very computationally expensive which makes real-time implementation difficult, particularly in scaled devices which operate in higher frequency waves and therefore require higher sample times (Hals et al 2010;Richter et al 2013;O'Sullivan and Lightbody 2017).…”
Section: Introductionmentioning
confidence: 99%